2007
DOI: 10.1016/j.amepre.2007.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Physical Activity Patterns and Health-Related Quality of Life in U.S. Women

Abstract: Background-Despite studies showing that physically active individuals report higher quality of life scores, few data exist on the impact of changing physical activity levels on subsequent changes in quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
58
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 34 publications
12
58
0
5
Order By: Relevance
“…A previous study that examined the relationship between long-term physical activity and HRQOL reported that the more intense the physical activity, the stronger the relationship between physical activity and the physical aspects of HRQOL [30]. This suggests that engaging in high-intensity activity has an effect on the physical aspects of HRQOL.…”
Section: Discussionmentioning
confidence: 95%
“…A previous study that examined the relationship between long-term physical activity and HRQOL reported that the more intense the physical activity, the stronger the relationship between physical activity and the physical aspects of HRQOL [30]. This suggests that engaging in high-intensity activity has an effect on the physical aspects of HRQOL.…”
Section: Discussionmentioning
confidence: 95%
“…In the studies conducted on both the young and the elderly, a positive relation was found between exercise and being healthy. It was argued that physically active individuals are healthier than their sedentary peers and feel better themselves (16,30). In another research by Gillison et al (10), it was stated that light and moderate intensity exercises done for 3-6 months contributed to physical and mental health (10).…”
Section: Discussionmentioning
confidence: 99%
“…Tratando-se de adolescentes, ela exerce papel fundamental na prevenção e controle da obesidade, doenças cardiovasculares, câncer de cólon em mulheres, doença da vesícula biliar e síndrome metabólica (2,3) . Apesar disso, a inatividade física prevalece elevada e parece afetar crianças e adolescentes em diferentes regiões brasileiras (4,5) .…”
Section: Introductionunclassified